Sustainability Analysis Of Gerinsing Weaving Industry: Probability Approach - Saskara, Ida Ayu Nyoman; Purwanti, Putu Ayu Pramitha (Jurnal Ekonomi Kuantitatif Terapan, 2023)
The  gerinsing weaving (tenun gerinsing) craft industry is a culture-based creative industry that has its own values ??and characteristics as a local cultural heritage. It can also link traditional knowledge with innovation and creativity which is considered important for a number of developing countries because it has economic potential and has an impact on economic development. Karangasem as one of the regencies in Bali which is full of culture-based woven crafts industries such as geringsing woven fabrics.There are many stakeholders who care about and have an interest in the sustainability of the gringsing weaving industry. The existence of uncertainty also cannot be ruled out to maintain its sustainability. The objectives to be achieved in this study are: 1) to determine the probability scenario of grinsing weaving sustainability; 2) to determine the sensitivity of scenarios driving the sustainability of grinsing weaving in Tenganan Pegringsingan Village, Karangasem.             Primary data were obtained from respondents through distributing questionnaires to craftsmen, consumers and stakeholders. The distribution of this questionnaire is a survey to obtain data as a comparison of the results of Focus Group Discussion (FGD) with experts who will later determine the probability scenario of sustainability. The prospective analysis used in this study is the SMIC-Prob analysis. ResultsThe analysis shows that of the four (4) scenarios formulated as a result of the FGD with experts, there is a combination of scenarios with the highest conditional opportunity, namely the 1101 combination, which means that the scenario of craftsmen producing as usual, apart from producing, also side comersial, and reducing production is the best combination with probability 0.124. While the sensitivity of the scenario is shown with the highest elasticity results in the increase scenario (increasing production) of 1.422, which is heavily influenced by the scenario of continuing to produce as usual of -0.624, which means that every 100% increase in the chance of producing as usual will reduce the chance of craftsmen increasing production by as much as 62.4 percent.